Influence of Rosa damascena hydrosol on skin flora (contact culture) after hand-rubbing - Bayhan, Gulsum Iclal; Gumus, Tulay; Alan, Basak; Savas, Isil Kubra; Cam, Saliha Aysenur; Sahin, Elif Ayca; Arslan, Seyfullah Oktay (GMS hygiene and infection control, 2020)
Aim and Introduction: Rosa damascena is one of the most well-known species of the Rosaceae family and is widely used in the food and perfume industry. Rose hydrosol is a product which is produced by distillation of rose petals. There is very little research about the antimicrobial effect of rose hydrosol. In this study, we aimed to investigate the antibacterial effect of Rosa damascena hydrosol in vivo. Method: 45 adult volunteers who were not healthcare workers were included in this study. Exclusion criteria included existing skin disorders or lacerations, pregnancy, presence of nail polish, recent handwashing or use of antiseptic lotion/soap in the last week, and antibiotic use in the last 3 months. At baseline, each subject was asked to rub the fingertips of the dominant hand on a sheep-blood agar plate. The subjects were randomly divided into two groups: one group rubbed their hands with 3 mL of alcohol-based hand antiseptic and the other group with 3 mL of rose hydrosol. Following sample collection, the subjects were asked to rub their hands according to the World Health Organization's (WHO) "How to Hand Rub" technique. After the hand-rubbing sequence, the hands were allowed to air-dry and fingertip sampling was performed. Culture plates were evaluated by a microbiologist blinded to group assignment. Rose hydrosol was analysed by gas chromatography/mass spectrometry. Results: The main components of rose hydrosol are phenyl ethyl alcohol, beta-citronellol and geraniol. Of the total of 45 participants, 23 were included in rose hydrosol group and 22 in the alcohol-based hand-rub group. The colony counts decreased significantly in the alcohol-based solution group after hand-rubbing, whereas there was no significant reduction in the rose hydrosol group. Conclusion: A number of studies have shown good antimicrobial activity in rose products, especially in rose oil, but we found no antibacterial effect of rose hydrosol after hand-rubbing. However, it must be borne in mind that the amount and types of rose hydrosol components are highly influenced by the given agro-meteorological conditions and technological production methods.Aim and Introduction: Rosa damascena is one of the most well-known species of the Rosaceae family and is widely used in the food and perfume industry. Rose hydrosol is a product which is produced by distillation of rose petals. There is very little research about the antimicrobial effect of rose hydrosol. In this study, we aimed to investigate the antibacterial effect of Rosa damascena hydrosol in vivo. Method: 45 adult volunteers who were not healthcare workers were included in this study. Exclusion criteria included existing skin disorders or lacerations, pregnancy, presence of nail polish, recent handwashing or use of antiseptic lotion/soap in the last week, and antibiotic use in the last 3 months. At baseline, each subject was asked to rub the fingertips of the dominant hand on a sheep-blood agar plate. The subjects were randomly divided into two groups: one group rubbed their hands with 3 mL of alcohol-based hand antiseptic and the other group with 3 mL of rose hydrosol. Following sample collection, the subjects were asked to rub their hands according to the World Health Organization's (WHO) "How to Hand Rub" technique. After the hand-rubbing sequence, the hands were allowed to air-dry and fingertip sampling was performed. Culture plates were evaluated by a microbiologist blinded to group assignment. Rose hydrosol was analysed by gas chromatography/mass spectrometry. Results: The main components of rose hydrosol are phenyl ethyl alcohol, beta-citronellol and geraniol. Of the total of 45 participants, 23 were included in rose hydrosol group and 22 in the alcohol-based hand-rub group. The colony counts decreased significantly in the alcohol-based solution group after hand-rubbing, whereas there was no significant reduction in the rose hydrosol group. Conclusion: A number of studies have shown good antimicrobial activity in rose products, especially in rose oil, but we found no antibacterial effect of rose hydrosol after hand-rubbing. However, it must be borne in mind that the amount and types of rose hydrosol components are highly influenced by the given agro-meteorological conditions and technological production methods.